Two native pupal parasitoids of Ceratitis capitata (Diptera, Tephritidae) found in Spain - Falcó, José Vicente; Garzón-Luque, Eva; Pérez-Hinarejos, Marta; Tarazona, Ignacio; Malagón, José; Beitia, Francisco J. (IOBC/WPRS, 2020)
Searching native parasitoids of Ceratitis capitata is one of the activities carried out in the Valencian Community in plots of citrus and other fruit trees. Adults of two different species of hymenopterous insects have been obtained from medfly puparia reared under laboratory conditions. The pteromalids Spalangia cameroni Perkins and Pachycrepoideus vindemmiae (Rondani) have been identified as idiobiont pupal parasitoids of the Medfly.